Arte de caminhar na cidade: educando o olhar geográfico em andanças no centro de Campina Grande-PB - Bezerra, Daniel Almeida (2017)
It is in the contact of our body with the body of the city that, in a oriented and disoriented way, we construct the geographic knowledge. We construct it from readings - from books, from our contact with the theoretically systematized knowledge, but, eminently, we construct it through our daily spacial practices held in the geographical space of the city. The walks allow us to build a way of feeling, looking and thinking about the city. By walking, we learn to read the city, that is, to uncover its socio-spatial and playful dynamics. In these wanderings, if, in a deft mode, from the perspective of geographic research, we seek to reveal the city through excursions and the description of its space, in the erratic way, we reveal it through the urban narratives: of Cordel Literature, short film, chronicles, songs and poetry, composing together corpographic images of the city. In this horizon, we ask: How do the excursions and the drifting walk, in the city, contribute to the education of the geographic looking of teachers and students, and also, in the construction of a geographic-educational environment in the city center of Campina Grande-PB? How do these walking modalities exercise a dialogic function in the articulation between Geography Teaching and Geographic Education, between science and art, between ethics and politics, in the context of our urbanity put in check here? How do these walks in the city articulate themselves to the strategies of teaching and learning, of Geography and, at the same time, the urban game, of the walk adrift? How does drifting walk distinguish and, at the same time, articulate itself with the procedural concepts of geographic research? In these terms, we aim to investigate and understand the geographic space of Campina Grande-PB, together with the teachers and students of the Licensure degree in Geography (undergraduate and graduate) at UEPB and UFPB, from itinerant and errant walks in the city center, so that we propose its transformation - psychogeographical and corpographic - in a geographic-educational environment. Considering the articulation of these two movements from looking and walking, deft and erratic, we conducted an action research expressed in a set of five walks through the center of the city of Campina Grande-PB: four geographic expeditions and a drifting walk. Through them, we walked through squares, parks, streets and avenues, in a sort of dialogue with the speeches of the looking of teachers and students in a process of establishing a geographic-educational environment in this geographical space. In order to carry out these analytic-critical dialogues with the discourses of the other's looking, we use the Discourse Analysis theory in semi-structured interviews with the teachers, and for the discourses of the students‘ looking, we use the critical and dialogical analysis of their fieldnotes. We walk between science and art in the construction of a proposal of education of the geographic looking in the city. Therefore, we articulate elements of aesthetics, science, ethics and politics to compose new ways of being in the city - expressions of our urbanity and our own civility put into construction.